Juridical Review of Conditional Punishment for Perpetrators of Petty Crimes in Indonesia - Margaret Thatcher L; Achmad Adi Surya G.S; Hilyatul Asfia (Green Publisher Indonesia, 2026)
This study discusses the use of conditional punishment for people who commit minor crimes in Indonesia, with a focus on child protection as part of the juvenile criminal justice system. Parole is considered a form of restorative justice that not only emphasizes punishment, but also focuses on rehabilitation, education, and social reintegration of the perpetrator. This study discusses case number 6/Pid.Sus-Anak/2025/PN PSW which is a real example of the application of conditional punishment to children involved in acts of minor violence. The imposition of a conditional sentence is based on the perpetrator's age, psychological condition, support from family, and the good attitude shown by the perpetrator. This study uses a normative method by collecting secondary data from legal regulations, legal doctrines, and related court decisions. The results of the study show that conditional sentences are able to avoid the negative impact of detention while providing opportunities for perpetrators to improve themselves in a supervised manner. By applying the principle of